Pemahaman dan Penghayatan Toleransi Beragama Tokoh Tokoh Agama di Kelurahan Tumatangtang Kecamatan Tomohon Selatan Kota Tomohon - Marthinus Marcel Lintong; Agustinus Brayen Waluyan (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2023)
Acts of intolerance that often occur trigger a lack of respect between religious communities. This encourages researchers to find out how the understanding and appreciation of religious tolerance from religious leaders in the Tumatangtang Village, South Tomohon District, Tomohon City, as well as the efforts that can be made to help increase the understanding and appreciation of this religious tolerance. This study uses qualitative research with a descriptive approach. Data collection techniques used are observation, interviews and documentation studies. The data sources in this study were religious figures in the Tumatangtang Village. The results of the study show that religious tolerance as an attitude of accepting differences in the midst of diversity of religions and beliefs and is an act of respect and respect between adherents of religions, has been well understood. The appreciation of religious tolerance is seen as an obligation and becomes a lifestyle that is realized through concrete actions such as helping each other, accepting, appreciating, spreading love and care for others in order to form inter-religious harmony. Efforts that can be implemented to help increase the understanding and appreciation of religious leaders regarding religious tolerance are building inter-religious dialogue, building open cooperation with other religions, being actively involved in joint activities between religious communities and efforts to form interfaith organizations to know each other and be open with the teachings of faith from other religions or beliefs.